The nature of the intertext in flash fiction - Ashimova, Malika G.; Yermekbayeva, Aisulu Sh.; Aktanova, Aiman S.; Kaiyrbayeva, Zhazira K.; Kazhibayeva, Gulden K. (Opción, 2020)
The study aims to investigate the nature of the intertext in flash fiction. For this purpose, the concepts of intertext, intertextuality, reminiscence, allusion and their artistic nature, its various manifestations are analyzed in the stories of writers of the period of independence of Kazakhstan as a method. As a result, the blemish of the appearance of Bukir (Hunchback), who considered himself an incomparable artist, was reflected in his mind and feelings. In conclusion, writers criticized the character and his surroundings through death, exposing lies and truth and pursuing moral and aesthetic goals.